SMES'INNOVATION OF THE MEDIATOR OF THE INFLUENCE OF THE IMPLEMENTATION OF CSR PROGRAM ON COMPETITIVE ADVANTAGE OF SMES IN MALANG - Ratnawati, Ratnawati (Universitas Brawijaya, Indonesia, 2017)
The purpose of this study is to study the effect of CSR program implementation on SME innovation as a mediator of CSR program influence of competitiveness of Competitive Small Medium Enterprises in Malang City. The analysis unit used is Small and Medium Enterprises (UKM) located in Malang City which gets CSR program from Government or Private sector of 198 SMEs, out of 460 SMEs who received assistance from the CSR program. Analytical tool used is Structural Equation Modeling (SEM). The results show that partnerships with government and private parties through CSR programs can contribute to the improvement of innovation for SMEs, through innovation of products, processes and business systems of SMEs, so as to create competitive advantage.